PENGEMBANGAN HOME INDUSTRI PENGOLAHAN JAMUR TIRAM DALAM MEMBUKA PELUANG USAHA BARU DI KABUPATEN PAMEKASAN - Matsaini, ST., MT; Sholeh Rachmatullah; Alfi Hasaniyah (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2022)
Home industry is an independent business unit carried out by a group of people in a family. One that is included in the Home industry category is UD.WARAS with the type of oyster mushroom farming business. The packaging of oyster mushroom agricultural products is packaged in plastic and bound using an electric transformer modified with wires that are far from K3 elements. At the peak of harvesting, many mushrooms are not selling well in the market due to the many competitors from outside the region and the packaging that is less attractive than the competitors' packaging. In this PKM, it seeks to develop a home industry by providing packaging equipment in the form of a vacuum cleaner. The method in this PKM provides training on product packaging with a vocum cleaner, provides assistance to create new product packaging by adding better stamps and stickers, provides directions for making oyster mushroom crispy crackers, and explains the importance of digital marketing in this digitalization era.